Romanticism and the human sciences : poetry, population, and the discourse of the species - McLane, Maureen N. (Cambridge studies in Romanticism, 2000)
"This study examines the dialogue between British Romantic poetry and the human sciences of the period. Maureen McLane reveals how Romantic writers participated in a new-found consciousness of human beings as a species, by analysing their work in relation to major discourses on moral philosophy, political economy, and the emerging discipline of anthropology. The book offers original readings of canonical works, including Wordsworth's Lyrical Ballads, Mary Shelley's Frankenstein, and Percy Shelley's Prometheus Unbound, to show how the Romantics internalized and transformed ideas about the imagination, futurity, perfectibility, immortality, and population which so energized the moral and political debates of the period."--Jacket